2006
DOI: 10.1016/j.cardiores.2005.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac transgenic matrix metalloproteinase-2 expression directly induces impaired contractility

Abstract: Cardiac-specific, constitutively active MMP-2 expression leads to impaired contraction and diminished responses to inotropic stimulation. These findings indicate that MMP-2 can directly impair ventricular function in the absence of superimposed injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 35 publications
(36 reference statements)
6
69
1
8
Order By: Relevance
“…Although we have not determined molecular mechanisms in the present study, our findings are consistent with a recent report showing that GM6001 (a non-specific MMP inhibitor) prevented the cleavage of the N-terminus of the b 1 -adrenergic receptor [24]. Giving further support to our findings, increased MMP-2 expression impaired contraction and reduced the responses to inotropic stimulation in transgenic mice overexpressing MMP-2 [37,38]. Together, these findings strongly indicate that abnormal MMP-2 activity can directly impair LV function.…”
Section: Discussionsupporting
confidence: 92%
“…Although we have not determined molecular mechanisms in the present study, our findings are consistent with a recent report showing that GM6001 (a non-specific MMP inhibitor) prevented the cleavage of the N-terminus of the b 1 -adrenergic receptor [24]. Giving further support to our findings, increased MMP-2 expression impaired contraction and reduced the responses to inotropic stimulation in transgenic mice overexpressing MMP-2 [37,38]. Together, these findings strongly indicate that abnormal MMP-2 activity can directly impair LV function.…”
Section: Discussionsupporting
confidence: 92%
“…Thus these mice exhibited hemodynamic compensation in the basal state, although, as noted above, the response of isolated right ventricular trabeculae from these mice to inotropic stimulation was impaired (61). However, by 12 mo of age an increased mortality in the MMP-2 transgenic mice was evident, as were manifestations of overt congestive heart failure, including reduced activity, ascites, and cyanosis.…”
Section: Discussionmentioning
confidence: 71%
“…Taken together, the ultrastructural changes in the cardiac MMP-2 transgenic mice are most consistent with a primary cardiomyopathy phenotype. Support for this conclusion is provided by our recent observation (61) that isolated right ventricular trabeculae from MMP-2 cardiac transgenics exhibited impaired contractile force and diminished responses to inotropic stimulation. The contractile force of skinned trabeculae from MMP-2 cardiac transgenics was also diminished, consistent with a primary myofilament contraction defect.…”
Section: Discussionmentioning
confidence: 87%
“…Our previous study 10 and a recent study by Matsumura et al 22 have demonstrated that the inhibition of MMP 2 activity improves the survival rate after acute MI by preventing cardiac rupture and delays after MI remodeling. A recent study by Wang et al 23 has shown that cardiac-specific, constitutively active MMP 2 expression leads to impaired contraction and diminished responses to inotropic stimulation, indicating that MMP 2 can directly impair cardiac function in the absence of superimposed injury. Broad-spectrum pharmacological inhibition of MMPs significantly attenuated myocardial remodeling associated with chronic volume overload 3 or hypertension.…”
Section: Role Of Mmp 2 In Po Hypertrophymentioning
confidence: 99%